(3GdaGVdjIs - (3GdeQGOj , ehSi Hf GUHZ GdeQGOj GdbQWHj, CHh YeQGf,J (B321 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdQFjS CHh YeQGf bO TgQ ai GYUGQfG hai GbdjefG gPG Hd ai YOI CbGdje SjQI ehdGfG GdbGVi s
(3BNQgG (B:s
(3HCf jSbi eQi SYI ChbjI HhQb OQgejf edM gfOi fUa OQge hjUjQ Ydjg bOQ eG jSJbQ ai eYOJg Ke jJbjGg Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B35s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI eTgO (B(5115) s
Keywords: (3GdWHs